A review on gravity, antigravity, and gravitational shielding along with related prospective viewpoints and possible practical applications - Akaho, Eiichi (IJRDO-Journal of Applied Science, 2019)
Subjects on gravity, antigravity, and gravitational shielding are reciprocally related one another. However, we find very few papers which deal with this interrelated topic from the global standpoint. Gravity and gravity-related topics are one of the most intriguing pieces of area to physicists as an ever-lasting and interesting topic and they will continue to do so for many years to come. Einstein’s General Relativity equation is ingenious as far as the gravity concept is concerned. However, the contradiction between quantum mechanics and General Relativity has not yet been elucidated. Edwin Hubble reported in 1929 classical article on the expanding universe. By his finding the antigravity effect has been evidenced. Gravitational shielding devices have been reported by many researchers. At this point we would expect more powerful gravitational shielding devices will be developed in the near future. Based on this review articles, several prospective and practical concepts and ideas are presented including a cosmic elevator, use of sky-space for vehicles, and modified equation for gravity,